The effectiveness of the ETeMS programme and the effects on the teaching of Mathematics and Science in the classroom / Ahmad Faizal Tajuddeen - Tajuddeen, Ahmad Faizal (2006)
This study attempts to identify whether the ETeMS modules provide sufficient input for the Maths and Science teachers. Further it seeks to establish whether the teachers’ competency in both the subject matter and the new medium of instruction affect the teaching and learning process in the classroom and if the resources and materials provided by the government are adequate and suit the students’ level and ability in terms of the suitability of contents and language.The study was conducted on a group of 60 Mathemathics and Science teachers from the Primary and the Secondary schools in the District of Setiu, Terengganu.The method used in the paper was a survey using a set of questionnaires which comprised of four sections. The results show that the teachers whose their educational background is limited to SPM or Diploma level would find that the ETeMS course or module is very useful, But for those who had obtained a higher level of qualification would find that the ETeMS course is rather a waste of time. It was found that teachers’ competency in both the subject matter and English affected the teaching and learning process in the classroom and the resources and materials provided by the government are only found to be moderately adequate for classroom use. This paper hopes that the findings would provide fresh insight into the adequacy of the ETeMS module to enable educational planners to come up with an improved module